(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
With particular reference to developing nations like Nigeria, it is the objective of the paper to address the problem of the deficit of Office and Information Managers with appropriate employability skills for the 21st century cross-boundary labor market. Through the method of critical discourse and content analysis the paper analytically espoused the concepts of Office and Information Management, curriculum reform and cross boundary employability as a background to outlining the interplay between the phenomena of curriculum reform and cross-boundary employability in the 21st century.The paper established what it considered the key contents foundational to a viable curricular reform for employability across boundaries in the 21st century. In the final analysis the paper proffers adoption of appropriate policy frameworks for training Office and Information Managers for global relevance and competitiveness.